Characterization of silane treated and untreated natural cellulosic fibre from corn stalk waste as potential reinforcement in polymer composites. (15th August 2019) - Liu, Yucheng; Lv, Xueman; Bao, Jianlun; Xie, Jun; Tang, Xu; Che, Junjian; Ma, Yunhai; Tong, Jin
Highlights: Natural corn stalk fibres (CSF) were characterized in this work. Effects of silane treatment on the fibres were studied. 5 wt% saline treated CSF (316.3 ± 36.63 MPa) have better tensile strength. Silane treatment improved CSF-matrix bonding and impact strength of composites. This research confirms silane treated CSF as potential reinforcement in polymer composites. Abstract: Natural cellulosic fibres have significant potential as reinforcements to replace synthetic fibres applied in biopolymer composites. A natural cellulosic fibre was extracted from corn stalk waste and then it was treated by silane solution with different concentrations. The influences of silane on chemical, surface morphological and mechanical performances of Corn Stalk Fibre (CSF) as well as impact strength and impact fracture surface morphology of CSF reinforced polymer composites were evaluated in the present work. The chemical results showed that silane treatments remove a certain amount of hemicelluloses and lignin from the CSF surface, and increase the Crystallinity Index (CrI) and Crystalline Size (CrS) of the CSF. The CSF treated with 5 wt.% silane solution (5%STCF) presents a highest tensile strength of 223.33 MPa ± 41.22 MPa and Young's modulus of 18.98 GPa ± 2.43 GPa. The silane treatments can also improve the fibre-matrix interfacial bonding and enhance the impact strength of the polymer composites. The surface morphologies of the untreated and treated natural fibres and the impact fracture surface of the composites were examined by SEM.